Influence of Low-Cost Carriers on Airport Infrastructure Development - Pavlin, Stanislav; Dimnik, Igor; Starčević, Martin (Promet - Traffic&Transportation, 2007)
The European low-cost carriers share in passenger traffic isgetting higher each year. Their business model benefits frommany aspects. Still, one of the most important aspects is usageof secondary airports. Those airports are mainly regional incharacter with relatively low passenger figures. With arrival oflow cost carriers, traffic volume has greatly increased whichbrings additional load on airport infrastructure. Because of thisextra load, additional planning of future development as well asextension of movement surfaces, primarily apron area, and terminalareas is necessary.Several/ow-cost carriers currently operate to Croatian airports,and with forthcoming regulation liberalization theirnumber is expected to grow. The paper presents the increase inpassenger traffic at European and Croatian airports generatedby low-cost carriers, and its influence on development of airportinfrastructure.